Pengaruh Kepemimpinan Kepala Sekolah, Tunjangan Profesi Guru, dan Iklim Sekolah terhadap Kinerja Guru SMK Negeri di Kota Makassar - Askar Yaman (Madrasah Tsanawiyah DDI Cilellang, 2020)
This research aims to investigate how much the influence of principal’s leadership, teacher professional allowance and school climate affects teachers’ performance by addressing these five points: 1) how principals exercise their leadership skills; 2) how the teacher professional allowance works; 3) how the school climate is; 4) how teachers perform; 5) how much the aspect of principal’s leadership, teacher professional allowance, and school climate contribute to teachers’ overall performance. This research uses qualitative method and utilizes survey as the design. To explain the issue, it employs methodological approach with positivistic perspective and scientific approach through pedagogical and psychological perspectives. Total of 85 participants were selected from 610 population using accidental sampling technique. The data were collected using survey and documentations, then analyzed using Multiple Linear Regression Testing with three predictors. The data analysis in this research suggests some key findings: First, the principal’s leadership skill is on low range with score of 40%. Second, the teacher professional allowance is on moderate range with score of 48.2%. Third, the school climate is reported to be moderate with score of 32.9%. Fourth, the teachers’ performance is considered moderate with score of 40%. Fifth, the Multiple Linear Regression Testing reveals the influence rate of principal’s leadership, teacher professional allowance, and school climate on teachers’ performance is as follows: regression equation Ŷ=100.629+0.022X1+0.083X2+0.256X3, with Fcount of 4.661. The fact that Fcount is bigger than Ftable (2.72), and its sig value is smaller than 0.05 (0.005 < 0.05), it indicates that there is a significant influence of principal’s leadership, teacher professional allowance, and school climate on teachers’ performance are R = 0,384 and R2 = 0,116.